2008
DOI: 10.1021/ja803262w
|View full text |Cite
|
Sign up to set email alerts
|

Turn-On Fluorescence Sensing of Nucleoside Polyphosphates Using a Xanthene-Based Zn(II) Complex Chemosensor

Abstract: Fluorescence sensing with small molecular chemosensors is a versatile technique for elucidation of function of various biological substances. We now report a new fluorescent chemosensor for nucleoside polyphosphates such as ATP using metal-anion coordination chemistry. The chemosensor 1-2Zn(II) is comprised of the two sites of 2,2'-dipicolylamine (Dpa)-Zn(II) as the binding motifs and xanthene as a fluorescent sensing unit for nucleoside polyphosphates. The chemosensor 1-2Zn(II) selectively senses nucleoside p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
205
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(213 citation statements)
references
References 61 publications
7
205
0
1
Order By: Relevance
“…The published conditional Zn(II) binding constants of ZnAF-1 and ZnAF-2F were determined by competitive fluorescence titrations with NTA. 9,17 We additionally confirmed them by analogous competitive titrations, but using EGTA as a 15 competitor, 18 in the 100 mM Hepes at pH 7.4.…”
Section: Introductionsupporting
confidence: 61%
“…The published conditional Zn(II) binding constants of ZnAF-1 and ZnAF-2F were determined by competitive fluorescence titrations with NTA. 9,17 We additionally confirmed them by analogous competitive titrations, but using EGTA as a 15 competitor, 18 in the 100 mM Hepes at pH 7.4.…”
Section: Introductionsupporting
confidence: 61%
“…Although this method was highly sensitive, it had major drawbacks including the need for an excitation wavelength in the ultraviolet range, which resulted in significant phototoxicity (23). The small molecular probe we used in the current study was developed in the laboratory of Dr. Hamachi (11,24). This ATP probe features a membrane anchor that has allowed us to attach the probe to the cell surface of living PMNs and to assess ATP concentration changes at the cell surface for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…7E). To assess concomitant intracellular ATP production, we used an intracellular ATP probe, 1-2Zn(II) that was also developed in the laboratory of Prof. Hamachi and is structurally identical to 2-2Zn(II), except that 1-2Zn(II) lacks the membrane anchor residue and can be taken up by cells (30). Using this probe, we found that mitochondrial firing in response to cell stimulation resulted in rapid bursts of intracellular ATP release, apparently by the release of ATP from activated mitochondria (supplemental Movie S8).…”
Section: T Cell Stimulation Triggers Mitochondrial Ros Production-mentioning
confidence: 93%